Health and Environmental Risks of Incense Smoke: Mechanistic Insights and Cumulative Evidence - Yadav VK; Malik P; Tirth V; Khan SH; Yadav KK; Islam S; Choudhary N; Inwati GK; Arabi A; Kim DH; Jeon BH (Dove Medical Press, 2022)
Virendra Kumar Yadav,1,* Parth Malik,2,* Vineet Tirth,3,4 Samreen Heena Khan,5 Krishna Kumar Yadav,6 Saiful Islam,7 Nisha Choudhary,8 Gajendra Kumar Inwati,9 Amir Arabi,3 Do-Hyeon Kim,10 Byong-Hun Jeon10 1Department of Microbiology, School of Sciences, PP Savani University, Surat, Gujarat, 394125, India; 2School of Chemical Sciences, Central University of Gujarat, Gandhinagar, 382030, Gujarat, India; 3Mechanical Engineering Department, College of Engineering, King Khalid University, Abha, 61411, Asir, Kingdom of Saudi Arabia; 4Research Center for Advanced Materials Science (RCAMS), King Khalid University, Abha, 61413, Asir, Kingdom of Saudi Arabia; 5Research and Development Centre, YNC Envis, New Delhi, 110059, India; 6Faculty of Science and Technology, Madhyanchal Professional University, Bhopal, 462044, India; 7Civil Engineering Department, College of Engineering, King Khalid University, Abha, 61411, Asir, Kingdom of Saudi Arabia; 8Department of Environment Science, School of Sciences, PP Savani University, Kosamba, Surat, Gujarat, 394125, India; 9Department of Chemistry, DP Chaturvedi College, Rani Durgavati University, Seoni, Madhya Pradesh, 480661, India; 10Department of Earth Resources and Environmental Engineering, Hanyang University, Seoul, 04763, South Korea*These authors contributed equally to this workCorrespondence: Byong-Hun Jeon, Email bhjeon@Hanyang.ac.krAbstract: Incense burning is practiced alongside many sacred rituals across different regions of the world. Invariable constituents of incense brands are 21% (by weight) herbal and wood powder, 33% bamboo stick, 35% fragrance material, and 11% adhesive powder. Major incense-combustion outputs include particulate matter (PM), volatile organic content, and polyaromatic hydrocarbons. The relative toxicity of these products is an implicit function of particle size and incomplete combustion, which in turn vary for a specific incense brand. Lately, the attention given to the Air Quality Index by international regulatory bodies has created concern about mounting PM toxicity. The uncharacteristically small physical dimensions of these entities complicates their detection, and with no effect of gravity PM fractions rapidly contribute to oxidative stress, enhancing random biochemical reactions upon being inhaled. Incense burning generates four times the PM extent (45 mg•g− 1) of cigarettes (∼ 10 mg•g− 1). Several poisonous gases, such as CO, CO2, NO2, and SO2, and the unavoidable challenge of disposing of the burnt incense ash further add to the toxicity. Taken together, these issues demonstrate that incense burning warrants prompt attention. The aim of this article is to highlight the toxicity of incense-combustion materials on the environment and human health. This discussion could be significant in framing future policy regarding ecofriendly incense manufacture and reduced usage.Keywords: incense combustion, particulate matter, polyaromatic hydrocarbons, volatile organic content, oxidative stress, burnt incense ash